Uji Inter Rater Agreement pada Panduan Konseling Kelompok Kognitif Perilaku Bermuatan Nilai-Nilai Ta’lim Muta’alim untuk Mereduksi Perilaku Bullying Siswa MA - Burhani, Iqbal; Rahman, Diniy Hidayatur; Hidayah, Nur (Indonesian Journal of Counseling and Development, 2025)
This study aims to develop and evaluate a group counseling guide using the cognitive behavioral approach integrated with ta’lim muta’alim values to reduce bullying behavior among Madrasah Aliyah (MA) students. The background highlights the urgent need to address bullying, particularly within boarding school contexts, where students also function as santri, requiring culturally and religiously responsive interventions. The research adopted the Borg & Gall (1983) Research and Development (R&D) model, involving validation by experts in guidance and counseling, educational media, Islamic religious education, and end-users. The instrument was assessed using Gregory’s (2015) inter-rater agreement model to ensure accuracy, usefulness, practicality, and appeal. The results showed that the guide achieved a perfect agreement index (1.00) across all validation domains, indicating excellent relevance and applicability. Qualitative feedback from validators supported the integration of ta’lim muta’alim values such as discipline, respect, humility, and compassion as highly compatible with cognitive-behavioral techniques. The findings emphasize the novelty of culturally contextualized counseling by blending Western psychological methods with pesantren-based moral education. While the guide is highly effective for MA students, especially those in Islamic boarding schools, broader implementation in general high schools may require cultural adaptation. This research contributes to the innovation of counseling practices in Indonesia by offering a moral-religious framework that addresses behavioral problems like bullying in a holistic manner.